An Anatomy-Informed, Novel Technique for S1 Dorsal Root Ganglion Stimulation Lead Placement. Issue 10 (15th April 2022) - Chapman, Kenneth B; van Helmond, Noud; Kallewaard, Jan Willem; Vissers, Kris C; Patel, Kiran V; Motivala, Soriaya; Hagedorn, Jonathan M; Deer, Timothy R; Dickerson, David M
Abstract: Objective: A heightened and organized understanding of sacral anatomy could potentially lead to a more effective and safe method of dorsal root ganglion stimulation (DRG-S) lead placement. The aim of this technical note is to describe a standardized access method for S1 DRG-S lead placement. Design: Technical note. Methods: The described approach utilizes alignment of the lumbosacral prominence and is measurement-based, allowing for standardized sacral access, even when visualization is suboptimal. The medial-to-lateral needle trajectory is designed to limit interaction with the sensitive neural structures and allows for a more parallel orientation of the lead to the DRG and nerve root. Conclusions: The described technique potentially improves the safety of S1 DRG-S lead placement. The parallel lead orientation to the DRG may also increase efficacy while lowering energy requirements.